Analysis of the water network of the Yanayacu sub-basin, Ancash-Peru, 2022 (Aporte Santiaguino, 2022)
The research work was carried out in the sub-basin of the Yanayacu River (Ancash - Peru), its objectives were: to characterize the sub-basin of the Yanayacu River and the contrast of the existing empirical equations in the scientific literature related to the water network. The 20i Recuay digital charts and the Arcgis 10.8 software were used as materials. Horton's laws of channel number, mean channel length for a given order, and Melton's law were confirmed for the Yanayacu River sub-basin. Also, an exponential equation was obtained for the prediction of the total number of channels as a function of the channel order and a potential equation for the prediction of the total length of channels as a function of the total number of channels of a given order.Keywords: water network; Horton; Melton; number of channels; channel order
Keywords: Horton; Melton; number of channels; channel order